2004
DOI: 10.1080/00016480410017729
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of high alcohol and benzodiazepine consumption in sleep apnea patients studied with blood and urine tests

Abstract: Our findings correlate well with current views concerning alcohol and drug abuse in Sweden, and do not indicate that the frequency of such abuse is higher among OSAS patients. It should be noted that none of the patients who screened positive in the laboratory tests admitted to being alcohol or drug abusers when they consulted their physician. We recommend screening all OSAS patients for alcohol abuse using not only a questionnaire but also a laboratory test such as the CDT test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…2 The domains sleep subjective quality, latency, duration and efficiency, consumption of hypnotics and day dysfunction of the ICSP-VC used as insomnia markers were altered in a frequency much higher than that expected for the Colombian general population and according to what has been reported in the literature. 22,23 The anxious and depressive symptoms presented with higher frequency in the patients evaluated, similarly to what was expected among alcoholics. 20 According to the high prevalence of chronic insomnia found with the ICSP-VC in the studied population, alcoholics deserve medical care and treatment for their sleeping problem within their therapeutic plan.…”
Section: Discussionsupporting
confidence: 66%
“…2 The domains sleep subjective quality, latency, duration and efficiency, consumption of hypnotics and day dysfunction of the ICSP-VC used as insomnia markers were altered in a frequency much higher than that expected for the Colombian general population and according to what has been reported in the literature. 22,23 The anxious and depressive symptoms presented with higher frequency in the patients evaluated, similarly to what was expected among alcoholics. 20 According to the high prevalence of chronic insomnia found with the ICSP-VC in the studied population, alcoholics deserve medical care and treatment for their sleeping problem within their therapeutic plan.…”
Section: Discussionsupporting
confidence: 66%
“…28 Overall, therefore, the case is not strong for a direct relationship between alcohol use and development of OSA, though for people who have the condition, alcohol may worsen OSA symptoms. Physical exercise is a further candidate confounding variable.…”
Section: Possible Confounders and Effect Modifiers Affecting Prevalenmentioning
confidence: 99%
“…The results also showed that 6.6% of the patients had a history of opium use. In this regard, Nerfeldt et al reported that the prevalence of drug use among patients with obstructive sleep apnea syndrome (OSAS) was 3.2 % based on laboratory tests (20). Doctors can also consider this point in treating OSA patients.…”
Section: Discussionmentioning
confidence: 99%